Food Iron Absorption Measured by an Extrinsic Tag - Cook, J. D. (1972)
The paper describes the use of an extrinsic tag of inorganic radioiron to determine the total absorption of nonheme iron from a complete meal. The method was developed by measuring the iron absorbed from vegetable foods containing biosynthetically incorporated (55)Fe (intrinsic tag) and from (59)Fe added as a small dose of inorganic iron to the same meal (extrinsic tag). In studies with maize, black bean, and wheat, a consistent extrinsic: intrinsic radioiron absorption ratio averaging 1.10 was observed. Similar results were obtained with either ferrous or ferric iron as the extrinsic tag, and with doses of the latter ranging from 0.001 to 0.5 mg iron added to a test meal containing 2-4 mg of food iron. Adding the radioiron at different stages in preparation of the test meal also had little effect. Separate administration of the extrinsic tag was less satisfactory when small portions of a single food were employed, but with a complete meal, the separate dose was preferable. The extrinsic tag provided a valid measure of absorption despite marked differences in the iron status of the subject, and with wide changes in absorption imposed by adding desferrioxamine or ascorbic acid to the test meal. These findings indicate that there is a common pool of nonheme iron, the absorption of which is influenced by various blocking or enhancing substances present in the meal.